Instructional Design For The Teaching English To Young Learners At Sdit Ulul Albab 02 Purworejo - HERLY SUTANTI, IKHA; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D (2015)
This study aimed to discover the existence of instructional design for young learners in SDIT Ulul Albab 02 Purworejo. The purpose of this study was to describe the instructional design for young learners at Integrated Islamic Elementary School (SDIT) of Ulul ALbab 02 Purworejo which includes syllabus, learning objectives, teaching design and assessment. The object of this research is the students of SDIT Ulul Albab 02 Purworejo. This research is qualitative research. Instructional materials are divided into printed and unprinted materials. Teaching design is divided into the role of teacher, the role of student, class procedures and class activities. Media are grouped into two forms, the first is the print media such as images, colorful paper, etc; the second is the media that has not been printed in the form of a tape recorder, a video or a slide. Assessment models namely the completion of the task dialog, multiple choice and reading tasks. The type of evaluation is formative and summative evaluation. Based on the findings, discussion, conclusions and implications, the writer suggest to the teachers of English to further encourage the involvement of students in the classroom. Application of the method varied so as to create an active and fun learning, clear technique is also needed in the teaching of English. The writer also recommends for future researchers in order to expand studies in other studies.